Children's Literature, Popular Culture, and Robinson Crusoe - O'Malley, A. author. aut Link
XII, 195 p.
Keywords: This study of the afterlife of Robinson Crusoe offers insights into the continued popularity and relevance of Crusoe's story and how modern conceptions of childhood are shaped by nostalgia and ideas of 'the popular'. Examining many adaptations in a variety of formats, it reconsiders the place Crusoe has occupied in our culture for three centuries.